Manual for Use of Al-rich Residues in Law CO2 Mineral Binders - Vojo Jovanov, Biljana Angjusheva, Emilija Fidanchevski (Slovenian National Building and Civil Engineering Institute, 2020)
This manual addresses the legislative aspects, governing the use of secondary raw materials in construction products, description of the most common Al-containing industrial and mining residue (bauxite deposits, red mud, ferrous slag, ash and some other by products from industry), potentiality for their reutilisation and its economic aspects, potential requirements/barriers for the use of secondary raw materials in the cement industry and a description of belite-sulfoaluminate cements, which are a promising solution for implementing the circular economy through the use of large amounts of landfilled Al-rich industrial residue and mining waste cement clinker raw mixture. This manual was prepared by partners of the RIS-ALiCE project. It provides a popular content, which targets relevant stakeholders as well as the wider society. Moreover, it offers education material for undergraduate, master and PhD students.
RECYCLING POSSIBILITIES
Keywords: Al-rich residues, fly ash, bottom ash, red mud, slags, recycling